Peran Orang Tua Dalam Mencegah Pernikahan Dini di Desa Cakul Kecamatan Dongko Kabupaten Trenggalek - Azzahra, Diovina; W, Warsono (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Marriage in Indonesia is legal only if both parties have reached the age of 19, according to Law No. 16 of 2019. Divorce often occurs in cases of early marriage, which can affect the future of the child. Therefore, efforts to prevent early marriage need to be made, especially at the most basic level, namely the family. The obligation to protect children from the threat of early marriage rests entirely on the shoulders of the family, the most basic social unit. Parents from the father or mother are discussed here. This study aims to examine various preventive measures and identify the role of parents in preventing early marriage. This study uses a qualitative strategy based on case study methodology to achieve this goal. The methods used are participant observation, in-depth interviews, and literature reviews. As a means of collecting information about the object being studied, observation requires careful observation or analysis of the surrounding environment. Interviews allow researchers to obtain data related to the topic through direct question and answer sessions with informants. The study relies on photo documentation as one of the real evidence. Parents in Cakul Village, Dongko District, Trenggalek Regency, can help reduce the number of early marriages by setting a good example, educating their children both formally and informally, providing advice and an overview of the lives of parents who marry young, setting time limits for going out of the house, regulating their circle of friends, communicating frequently and openly, giving children trust within reasonable limits, and instilling a sense of responsibility and discipline from an early age. Efforts like these can help parents in Cakul Village slow down the alarming increase in the number of underage brides each year in Indonesia.